TNF-ALPHA AND SERUM GALECTIN-3 IN NON DIABETIC PATIENTS WITH HEART FAILURE WITH PRESERVED LEFT VENTRICULAR EJECTION FRACTION - Bolotskykh, A. V.; Rudyk, Yu. S.; Udovychenko, M. M.; Lozik, T. V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
Insulin resistance (IR) leads to structural abnormalities in the heart. Purpose of the study is to investigate the levels of serum Gal-3 levels (sGal3), THF-alpha (TNF-a), Nt-proBNP, HOMA index and insulin and their relationships in non-diabetic patients with heart failure with preserved left ventricular ejection fraction (HFpEF). Forty five non-diabetic patients (27 males and 18 females; mean age 60.4.1±9.7 years) with HFpEF were examined. Patients with diabetes mellitus were excluded. The serum sGal3, TNF-alpha, Nt-proBNP and insulin levels measured in serum by ELISA, according to manufacturer’s instructions. Homeostasis Model Assessment (HOMA) index was calculated as a measure of IR at fasting state (IR=fasting glucose × fasting insulin/22.5).The echocardiographic parameters were measured with M- and B-mode and calculated following the American Guidelines of Echocardiography Society. Continuous variables are expressed as median (25th, 75th percentile). For nonparametric Spearman’s correlation analysis and Mann-Whitney U test were used. All statistical tests were 2-tailed, and p < 0.05 was considered statistically significant.It was found, that IR often occurs in non-diabetic patients with HFpEF. The sGal3, TNF-alpha and insulin are significantly increased in HFpEF patients with IR and without T2DM our study shows an association of the IR, TNF-alpha and sGal3 with echocardiographic parameters in the non diabetic with HFpEF. This fact may indicate the influence of IR on fibrogenesis process and thus facilitate the processes of myocardial remodeling.